PENGARUH KUALITAS PRODUK, HARGA, DAN KEAMANAN DATA SIMCARD INDOSAT TERHADAP LOYALITAS MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS PGRI WIRANEGARA - Nurul Aini Agustina; Sugeng Pradikto; Nurus Sobakh (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Indonesia communication technology services have undergone quite rapid development and growth, in communication technology, there are means to become a cellular (wireless) telecommunication service which we usually call Simcard. For this reason, good quality, affordable prices are needed so that they can compete with other product brands and data security so that consumer data is not leaked and spread to other people. The purpose of this study was to understand the effect of product quality, price and data security on Indosat simcards on student loyalty in the economics education study program at PGRI Wiranegara University. This type of research is quantitative research using descriptive analysis. The instrument used in this study was a questionnaire/questionnaire using 57 samples. The analysis used in this research is multiple linear regression analysis and classical assumption test followed by partial test and simultaneous test. The results obtained in this study indicate that: (1) There is a partial positive and significant influence between the quality of Indosat simcard products on student loyalty in the Economics Education Study Program at PGRI Wiranegara University. (2) There is a partial positive and significant influence between Indosat simcard prices on Student Loyalty in the Economics Education Study Program at PGRI Wiranegara University. (3) There is a positive and significant influence between Indosat simcard Data Security partially on Student Loyalty of the Economics Education Study Program at PGRI Wiranegara University. (4) There is a positive and significant effect simultaneously between Product Quality, Price, and Indosat Simcard Data Security on Student Loyalty in the Economics Education Study Program, Pgri Wiranegara University.